Minimasi Biaya Perawatan Mesin VIS Pulper Pengupasan Biji Kopi dengan Menggunakan Metode Preventive Maintenance Di PTPN XII Ngrangkah Pawon - Hariono, Budi; Prabawati, Annisa Dian (Jurnal Teknik Terapan, 2023)
The development of industrial technology requires companies to be able to use existing resources. The most important thing in the production process is the machine. PTPN XII Ngrangkah Pawon is a limited liability company owned by the Republic of Indonesia and PT Perkebunan Nusantara III (Persero). The use of machines is also used in the PTPN production process. The purpose of this research is to find out whether it is possible to minimize the cost of maintaining the vis pulper machine through preventive maintenance and repair maintenance methods. This type of research is carried out quantitatively by observing and studying the material obtained during the production process for three years (2020-2022). This research was conducted offline for 1 month starting from early July to August. Data analysis was carried out using two methods, namely repair policies and preventive policies. maintenance using repair maintenance with a period of 3 years, namely in the production process by repair calculation in May 2020 the results were Rp. 497,354/week while calculating maintenance cost preventive maintenance results obtained Rp. 708,817/week by scheduling every 4 weeks. For the results of treatment repair calculation maintenance in May 2021 the production process obtained a result of Rp. 6,797,131/week while on preventive maintenance get the calculation results of Rp. 8,508,950/week with scheduling once a week. Finally, in 2022, in May, the calculation results were obtained using repair maintenance Rp. 373,089/week while on preventive maintenance Rp. 524,366/week with a schedule of 4 weeks. Based on the results of the calculations it is explained that minimizing costs using the method of preventive maintenance can be applied, but to get a cheaper fee it is better to use a repair policy maintenance because the estimated results of spending calculations are cheaper compared to using maintenance expenses for preventive maintenance.